The Interrelation between the Interest Groups and Their Impact on the Economic Reforms in Modern Russia - ЯковлевАндрей Александрович (Journal of Economic Sociology, 2010)
The end (look for the first part: Т. 4, № 5, 2003). The first part of the book has been devoted to the main approaches to the analysis of the social background of the reforms discussed in the previous research findings. This part provides the issues that have not been covered yet. The reasons for taking the particular way of the reforms’ development of a country remain unclear as well as the ways out of the traps of partial reforms and political polarization. The author thinks that the significant role is played by the initial differences in social and institutional structures of the transition countries. The author tries to explain the elites’ evolution by the structural switches in the beginning of the 1990s. The paper deals with the analysis of the interaction mechanisms between the authorities and business (and business and political elites). The author assumes that at the same time several strategies for alternative ways of development are possible not only that dominating one. These strategies always depend on the particular interests of both the business and the state. Taking into account such strategies will let us answer the question of what social groups are able to support the reforms and the policy of economic growth under the conditions of the «bad equilibrium» – in the way of “state privatization” and “political polarization”.